Cone and seed properties in a young and an old stand of Pinus sylvestris L. - Bergsten, Urban (1985)
Cones from a young (24-28 years) and an old stand (120-280 years) of Pinus sylvestris L., orignating from Lycksele in north Sweden (N 64o 45´, Alt. 310 m) were examined in the laboratory to establish whether there are biological restrictions on the use of seeds from young stands. The number of cones per ha was approximately 71 000 in the old stand and about 29 000 in the young stand, which corresponded to 4.3 respectively 2.1 kg of filled seeds. Cones from the young stand exceeded cones from the old stand in length, volume and dry weight; consequently the seeds from the young stand were heavier than those from the old stand. There were no differences between the two stands in other properties, such as germination rate and capacity, number of seeds per cone, percentage of empty seeds and extractability. There appears to be no biological reason for restricting cone collection from a young stand of the above age.